2011
DOI: 10.1126/scitranslmed.3001564
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin Deficiency Protects Against Pulmonary Fibrosis in Mice and Prevents Fibroblast Invasion of Extracellular Matrix

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive disease causing unremitting extracellular matrix deposition with resultant distortion of pulmonary architecture and impaired gas exchange. β-arrestins regulate G-protein-coupled receptors through receptor desensitization while acting as signaling scaffolds that facilitate numerous effector pathways. Here we examine the role of β-arrestin1 and β-arrestin2 in the pathobiology of pulmonary fibrosis. In the bleomycin-induced mouse lung fibrosis model, loss of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 58 publications
(96 reference statements)
2
99
0
Order By: Relevance
“…26 Another recent study showed that knockdown of b-arrestin2 in fibroblasts from IPF patient attenuated the invasive phenotype. 27 We also observed that the cells exhibiting moderate or strong amount of actin filaments had more active invasion than the cells with low amount of intracellular actin filaments and that the invasion of the cells cultured from the patients with IPF correlated positively with both mRNA and protein levels of a-SMA. Also in NSIP a-SMA mRNA levels correlated with the invasion.…”
Section: Discussionmentioning
confidence: 48%
“…26 Another recent study showed that knockdown of b-arrestin2 in fibroblasts from IPF patient attenuated the invasive phenotype. 27 We also observed that the cells exhibiting moderate or strong amount of actin filaments had more active invasion than the cells with low amount of intracellular actin filaments and that the invasion of the cells cultured from the patients with IPF correlated positively with both mRNA and protein levels of a-SMA. Also in NSIP a-SMA mRNA levels correlated with the invasion.…”
Section: Discussionmentioning
confidence: 48%
“…Another report also mentioned that -arrestins mediate fibroblast invasion and the development of pulmonary fibrosis (21). These results suggest that -arrestins can mediate anti-fibrotic and profibrotic pathways depending on stimulants, receptor, and cell types.…”
Section: Discussionmentioning
confidence: 90%
“…Second, previous reports showed that AngII-induced responses in cardiac fibroblasts and other fibroblast cell lines are different from those in cardiomyocytes in many aspects (9,19), which has led us to assume that SII-induced responses in fibroblast cell lines will be different from SII-induced responses in cardiomyocytes. Third, although -arrestin-biased agonists promote cardiomyocyte protection and reduce cardiac fibrosis (20), -arrestin signaling in different types of fibroblasts have been reported to initiate tissue fibrosis (21), and our own studies have found that -arrestin2 mediates metoprolol-stimulated cardiac fibrosis in vivo (22). Thus, SII may activate AT1R--arrestin signaling in cardiac fibroblasts and initiate cardiac fibrosis in the heart that could lead to cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In response to LPS, bone marrow-derived macrophages from ␤arr2 Ϫ/Ϫ mice show more IKK activity than WT macrophages (6), but they show equivalent LPS-induced secretion of the NFB-dependent gene products TNF and IL-6 (11). Although ␤arr2 appears to reduce secretion of TNF and IL-6 from fibroblast-like synoviocytes (13), it has no effect on the secretion of the NFB-dependent gene products (52)(53)(54) hyaluronan and plasminogen activator inhibitor-1 from lung fibroblasts (15). However, in SMCs, ␤arr2 augments TLR4-dependent IB degradation and inflammation-associated SMC proliferation (Fig.…”
Section: Discussionmentioning
confidence: 95%